USAHATANI DAN PENGOLAHAN KOPI ARABIKA DI DESA YAGARA DISTRIK WALESI KABUPATEN JAYAWIJAYA (Arabika Coffee Farming and Processing in Yagara Village Walesi District of Jayawijaya Regency) - Tuweben Wandik; Nordy F. L. Waney; Yolanda P. I. Rori (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
The purpose of this study was to describe the coffee farming and processing by Coffee Farmers in Yagara Village, Walesi District, Jayawijaya Regency, Papua. This research was conducted from September 2019 to November 2019. A sample of 20 respondents was selected using the simple random sampling method. Data analysis method used was descriptive method.The results showed that farming and processing of coffee beans including harvesting, stripping wet beans, fermentation, washing, drying and sorting of coffee beans in Yagara Village were still done traditionally.Keywords: coffee, farming, processing